Strengthening Religious Harmony through the Principle of the Middle Way in Indonesian Buddhism - Supriatna, Hendi; Ahmad Hambali, Radea Yuli; Rosyad, Rifqi (Prodi Studi Agama-Agama, 2025)
This research aims to examine the principles of moderation in Buddhism and their application in the context of inter-religious harmony in Indonesia. The methodology used in this research is a religious approach using the Library Research method, included in the qualitative research category which collects data from primary and secondary sources. The analysis carried out is descriptive analytical, aiming to interpret existing conditions. The findings of this research indicate that Buddhist teachings, which emphasize universal love, dialogue, deliberation, and the concept of the middle way, are a very important foundation for creating religious harmony. This concept firmly rejects extremism and encourages transformation towards salvation through the practice of simplicity. However, there are significant challenges in implementing moderation in inter-religious dialogue, such as reluctance from some religious groups, emotional conflicts, and limitations in verbal communication. Therefore, it is important to pay attention to non-verbal aspects of communication and involve all parties to create an environment conducive to constructive dialogue. With sustainable understanding and practice, it is hoped that harmony and peace can be built amidst the diversity of religions and beliefs